الفكر الاستراتيجي والأمني في الجزائر: بين النضج السلوكي والجفاء التنظيري - نسيم, بهلول (University of Eloued جامعة الوادي, 2020)
إن أغلبية بلدان العالم الثالث كثيرا ما تعاني من فقر في أي شكل من أشكال التفكير الإستراتيجي وهذا في دائرة اهتماماتها وأولوياتها. وكذا الوعي بأهمية هذا النوع من التفكير. ومن هنا يغيب التخطيط للمستقبل وتغيب البرمجة والإستشراف والتدبير الإستباقي للأمور. وبالنتيجة تسير سياسات تلك الدول على غير هدى وبدون خرائط طريق مستلهمة من دراية بالمسارات التي قد تسلكها الأحداث في العالم ومن المعرفة بالملامح التي قد تتسم بها السياقات الدولية. مما يتسبب في انتهاج سياسات عشوائية تتصف بالتلقائية والإرتجالية والتخبط. فالدول التي تفتقر لذهنية استراتيجية واضحة وتخطيط استراتيجي سليم لن تشكل قوة يعتد بها، مهما بلغ تفوقها بعناصر قوتها الثابتة والمتغيرة وستكون محصلة معادلة القوة لديها ضعيفة، وأقل من مثيلاتها من الدول الأخرى، ذات نفس عناصر القوة الثابتة والمتغيرة. ومن هذا الباب سيعكف هذا المقال على دراسة وتحليل مكانة الذهنية الاستراتيجية والتفكير الاستراتيجي من واقع اهتمامات وأولويات المؤسسات السيادية في الجزائر وعلى رأسها المؤسسة العسكرية. وموقع النخب الأكاديمية ودورهم – إن وجد – في ترقية هذا الشكل من أشكال التفكير النساني والذي من شأنه أن يحقق الريادة الإستراتيجية للدولة والمجتمع معا، كمرحلة من مراحل التفوق الداخلي والخارجي الذي تصل إليه الدولة، كمجموعة من النتاجات والمخرجات الناجمة عن مجموعة من الأسس النظرية والتطبيقية لرؤى ما تتسم بالنضج وفق حسابات القوة والتأثير الإستراتيجي. The majority of Third World countries often suffer from poverty in any form of strategic thinking, even within the scope of their concerns and priorities, as well as awareness of the importance of this type of thinking, hence the absence of planning for the future and the absence of foresight and proactive management of things. As a result, their policies are not guided by roadmaps inspired by awareness of the direction of events in the world and of the features of 2020 543 518 01 11 519 international contexts. This leads to the adoption of random policies that are spontaneous, improvised and confused. Countries that lack a clear strategic mentality and sound strategic planning will not be a force to be reckoned with, regardless of their superiority with fixed and variable strengths, and the result of the equation of power for them will be weak and less than those of other states, with the same elements of constant and variable power. From this standpoint, this article will study and analyze the status of strategic mentality and strategic thinking from the reality of the concerns and priorities of the sovereign institutions in Algeria, especially the military, and the position of the academic elites and their role—if any—in promoting this form of human thinking, which would achieve the strategic leadership of the state and society altogether, as a stage of internal and external excellence reached by the state as a set of outcomes and outputs from a set of foundations of theoretical and practical of strategic visions, often characterized by maturity on the basis of strength and strategic influence.
مجلد11، عدد1
Keywords: الفكر؛ الجزائر؛ العسكرية؛ الأمن؛ الاستراتيجية.; Thought; Algeria; Military; Security; Strategy.